Direct proof of polynomial complexity optimum multiuser detection algorithm - Reid, A B; Grant, A J; Alexander, P D (Electronics letters, 2001)
A new approach to the polynomial complexity optimal detection algorithm for certain synchronous multiple access systems was presented. Identification of properties of signature signal matrices leading to polynomial complexity algorithm was performed. It was observed that optimum detector makes a decision on the transmitted signal in each symbol interval such that the probability of a correct decision is maximized.